2005
DOI: 10.1111/j.1365-2672.2004.02474.x
|View full text |Cite
|
Sign up to set email alerts
|

Link between spatial structure of microbial communities and degradation of a complex mixture of volatile organic compounds in peat biofilters

Abstract: Aims: To investigate the relationships between the operation of the volatile organic compound (VOC) removal biofilter and the structure of microbial communities, and to study the impact on degradation activities and the structuring of microbial communities of biofilter malfunctions related to the qualitative composition of the polluted air. Methods and Results: A microbiological study and a measurement of biodegradation activities were simultaneously carried out on two identical peat-packed columns, seeded wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 34 publications
4
66
0
Order By: Relevance
“…A plausible explanation is that the CBP biofilter developed a different consortium of microorganisms, which was able to degrade toluene faster than the populations in the other reactors. This is consistent with the observations of Li and Moe, 21 who found differences in DGGE band patterns along the axial direction and between reactors depending on their operating modes, as well as those of Khammar et al, 22 who used single-strand conformation polymorphism analyses and found that different communities developed in two parallel biofilters. They further showed that the distribution of the biodegradation activity correlated with the local microbial density and diversity.…”
Section: Detailed Packing Analysissupporting
confidence: 81%
“…A plausible explanation is that the CBP biofilter developed a different consortium of microorganisms, which was able to degrade toluene faster than the populations in the other reactors. This is consistent with the observations of Li and Moe, 21 who found differences in DGGE band patterns along the axial direction and between reactors depending on their operating modes, as well as those of Khammar et al, 22 who used single-strand conformation polymorphism analyses and found that different communities developed in two parallel biofilters. They further showed that the distribution of the biodegradation activity correlated with the local microbial density and diversity.…”
Section: Detailed Packing Analysissupporting
confidence: 81%
“…The BOD value of German RDF pellets was lower than that of Japanese RDF pellets, although the plastic content in the former was lower than that in the latter, indicating that the German RDF pellets contained lower amounts of organic materials easily consumed by microorganisms. 7) It is likely that the biodegradation process in the German plant reduced the amounts of fermentable organic materials. The water content of both RDF pellet sample types was low, and the strength of the German RDF pellets was higher than that of the Japanese ones.…”
Section: Resultsmentioning
confidence: 99%
“…In general, Actinobacteria are often found to be a quantitatively important part of the microbial community in biofilters treating VOC (15) and were also found to constitute up to 16% of the total community in a similar air filter treating exhaust air from a pig farm (26). The aerobic Gordonia and Rhodococcus have previously been detected by cultivation in biofilter communities (23), and several other genera of Actinobacteria such as Dietzia, Gordonia, Janibacter, and Rhodococcus are known to oxidize butyric acid as detected in pure culture studies (4,7), but the ability has not yet been shown with in situ experiments. Furthermore, Gordonia has previously been associated with the degradation of hexane using stable isotope-based phospholipid fatty acid analysis on a biofilter treating air from an oil mill (13), which could suggest a more general role for species of this genus.…”
Section: Discussionmentioning
confidence: 99%